J/ψ production cross section and its dependence on charged-particle multiplicity in p + p collisions at √s=200 GeV - STAR Collaboration (Physics Letters B, 2018)
We present a measurement of inclusive J/ψ production at mid-rapidity (|y|¡1) in p+p collisions at a center-of-mass energy of s=200 GeV with the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The differential production cross section for J/ψ as a function of transverse momentum (pT) for 0¡pT¡14 GeV/c and the total cross section are reported and compared to calculations from the color evaporation model and the non-relativistic Quantum Chromodynamics model. The dependence of J/ψ relative yields in three pT intervals on charged-particle multiplicity at mid-rapidity is measured for the first time in p+p collisions at s=200 GeV and compared with that measured at s=7 TeV, PYTHIA8 and EPOS3 Monte Carlo generators, and the Percolation model prediction.
Keywords: Charged-particle multiplicity; Multiple parton interactions; Quarkonium; collisions; dept.phy; p+p collisions; peer-reviewed